Índices reprodutivos e referencial teórico de equinos da raça mangalarga marchador - Fumagalli, Pedro Almeida Rezende (2020)
Mangalarga Marchador (MM) horses, with recognition of Brazilian origin, are approximately 200 years old since their appearance in the south of the state of Minas Gerais, from the crossing of Alter animals (coming from Portugal) with native mares. The option to work with the MM breed is due to the marked presence of this breed in the national herd and as a result of its geographical dominance in the country, being one of the breeds that is present throughout the national territory. All the work is built under the deductive analysis mode, where first a literature review is presented, in which relevant concepts are presented on the proposed theme, in which sources are used that address the theme presented, for later discussion of the data to the research carried out, where the collected data is pointed out and a discussion about them is created, in the demonstration of the case study.